Penerapan Metode Bermain Peran untuk Meningkatkan Pemahaman Siswa Terhadap Konsep Pecahan Sederhana pada Mata Pelajaran Matematika di SD Inpres I Nambaru - Ana Agung Made Ardani (Universitas Pendidikan Mandalika, 2021)
The purpose of this study was to analyze the impact of implementing role playing methods in learning mathematics on improving learning outcomes and student activeness in the basic material of simple fractions. This research method uses classroom action research. The data source came from grade III students of SD Inpres I Nambaru, totaling 24 students. Data collection techniques through formative test results. Data analysis was performed using quantitative and qualitative analysis, then consulted with the success criteria to determine student learning completeness. Based on the results of the formative tests from the first and second cycles, it was found that students' learning completeness had increased. From the initial cycle there were only 12 students out of 24 students or 50% who completed, then increased in the first cycle to 17 students from 24 students or 71%, and in the second cycle reached 100% completeness, namely 24 students completed out of 24 students. So that the conclusion obtained from this study is that the application of role playing methods in learning mathematics can improve learning outcomes and student activeness in the basic material of simple fractions